Pesticides: Routes of Exposure - Frederick M. Fishel (EDIS, 2016)
Pesticides can cause both short-term and long-term effects in humans. Human exposure to pesticides can happen through four major routes: through the mouth and digestive system, through the eyes, through the skin, or through the nose and respiratory system. This 2-page fact sheet explains each route of pesticide exposure, providing information on how to reduce the risk of pesticide exposure and hazard. Written by Frederick M. Fishel, and published by the Agronomy Department, December 2015.